Deteksi Financial Statement Fraud Berdasarkan Perspektif Pressure dalam Fraud Triangle - Muhammad Yunus; Ompon Lastiur Sianipar; Kharisma Yudha Saragih; Amelia Amelia (Owner : Riset dan Jurnal Akuntansi, 2019)
This study aims to determine the effect of the fraud triangle perspective illustrated by financial stability, external pressure, and financial targets on financial statement fraud on manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. This research is a type of causal associative research with a quantitative approach. The sample in this study were 49 Manufacturing Companies listed on the Indonesia Stock Exchange in 2015-2018. The type of data used in this study is secondary data. Data analysis method used in this study is Logistic Regression Analysis with the help of SPSS 25 software. The results obtained in this study indicate that external pressure has a positive and significant effect on financial statement fraud. Financial targets have a significant negative effect on financial statement fraud. While financial stability does not significantly influence financial statement fraud.